Intravitreal Injection of Splice-switching Oligonucleotides to Manipulate Splicing in Retinal Cells - Gérard, Xavier (Mol Ther Nucleic Acids, 2015)
Leber congenital amaurosis is a severe hereditary retinal dystrophy responsible for neonatal blindness. The most common disease-causing mutation (c.2991+1655A>G; 10–15%) creates a strong splice donor site that leads to insertion of a cryptic exon encoding a premature stop codon. Recently, we reported that splice-switching oligonucleotides (SSO) allow skipping of the mutant cryptic exon and the restoration of ciliation in fibroblasts of affected patients, supporting the feasibility of a SSO-mediated exon skipping strategy to correct the aberrant splicing. Here, we present data in the wild-type mouse, which demonstrate that intravitreal administration of 2'-OMePS-SSO allows selective alteration of Cep290 splicing in retinal cells, including photoreceptors as shown by successful alteration of Abca4 splicing using the same approach. We show that both SSOs and Cep290 skipped mRNA were detectable for at least 1 month and that intravitreal administration of oligonucleotides did not provoke any serious adverse event. These data suggest that intravitreal injections of SSO should be considered to bypass protein truncation resulting from the c.2991+1655A>G mutation as well as other truncating mutations in genes which like CEP290 or ABCA4 have a mRNA size that exceed cargo capacities of US Food and Drug Administration (FDA)-approved adeno-associated virus (AAV)-vectors, thus hampering gene augmentation therapy.